Gender, households and sustainability: Disentangling and re-entangling with the help of 'work' and 'care'. (September 2021) - Murphy, Joseph; Parry, Sarah
In rich, developed countries, many stakeholders are focusing on households as settings where progress can be made on environmental and sustainability issues. Related research, policies and interventions, however, tend to ignore gender dynamics, thus treating them as irrelevant, or exploit them to achieve sustainability goals. We challenge this regressive treatment and show how household sustainability can be progressive in relation to gender and sustainability simultaneously – doubly progressive. Specifically, we ask: How do gender and sustainability intersect in households? What are the normative implications of these intersections? To answer these questions, we disentangle the perspectives of 'work' and 'care', drawing on feminist and gender scholarship, and explore both in the domestic setting by focusing on sustainable technologies and sustainable consumption. In this way, the twin normative agendas of equality of work and expansion of care emerge as ways of linking gender and sustainability in households. Our conclusion considers tensions and overlaps between work and care to identify how they can be re-entangled. We argue that re-entangling work and care requires holding them in dynamic tension with care being the context for work and in this way a doubly progressive approach to household sustainability emerges.